STRATEGY DEVELOPMENT OF PUSKOPASKA IN THE ORDER OF MAINTAINING SOVEREIGNTY AND SECURITY THE UNITARY STATE OF THE REPUBLIC OF INDONESIA - Hary Nurdi; Iwan Vanany; Ahmadi Ahmadi (JOURNAL ASRO, 2021)
The development of science and technology as well as the strategic environment affects the demands for increasing the quality of the Indonesian Navy's human resources, the development of the Puskopaska to make soldiers with the knowledge and technology of weapons science and technology, which is very important, is carried out continuously. This is an effort to carry out the Puskopaska's vision, mission and goals as well as in order to increase the security and defense of the sea and coastal estuaries, therefore a Puskopaska development strategy is needed. The purpose of this research is to obtain factors, criteria, strategy formulation, prioritization and development strategy road map. The research method used is the analytical technique using the IFAS-EFAS matrix, SWOT matrix, QSPM matrix, and BORDA. The results of the study indicate that Puskopaska is in a defensive and guarding position so that the best strategy is to hold regular training programs and add certified trainers, as well as add weapons technology. With the Strength-Opportunity (SO1) strategy, (SO2), (SO3) followed by Strategy (ST1),(ST2),(WO),(WT)sorted by QSPM matrix to get priority strategy. The results of the QSPM matrix rank 7 (Seven) strategies, then grouped the rankings using the BORDA method, from the highest to the lowest scores as a step in starting the stages in the work plan for the next 5 (Five) years. Keywords: Puskopaska Organization, SWOT, BORDA